Evaluation of the Vitek MS ® system in the identification of KPC-type carbapenemase-producing Enterobacterales carrying the Tn4401a transposon (2022)
ABSTRACT: Identification of carbapenemase-producing clinical isolates is crucial for timely treatment guidance and control of in-hospital dissemination. Objective: To determine the diagnostic validity of the MALDI-TOF Vitek MS technique in the detection of KPC-type carbapenemases through the identification of the characteristic peak 11.109 Da in the mass spectrum, using PCR as a reference method. Methods: We evaluate 210 isolates, including 34 positive controls consisting of carbapenemase-producing Klebsiella pneumoniae isolates positive for the blaKPC gene, the pKpQIL plasmid and the Tn4401a transposon, 30 Enterobacteriaceae blaKPC isolates positive by PCR but of unknown plasmid background, and 146 negative controls. Agreement was established between MALDI TOF MS, the RAPIDEC® CARBA NP and modified Carbapenemase Inactivation Method (mCIM) test in conjunction with eCIM (p <=0.05) (95%CI); In addition, ROC curves and comparisons were made for each of these tests. Results: The 11.109 Da peak was detected in 100% of KPC Tn4401a positive isolates reaching sensitivity values of 100% (CI 98.53 - 100), specificity of 94.78% (CI 90.64 - 98.92), PPV of 82.93% (CI 70.19 - 95.66), NPV of 100% (CI 99.61- 100) and PVR of 19.14% (CI 9.31- 39.37). An agreement between the three diagnostic tests of 92.3% and a Kappa index of 0.8877 (CI 0.8112-0.9642) was obtained. Comparison of the ROC curves of the three tests showed AUC of 0.9714, 0.9786 and 0.971 for MALDI TOF, RAPIDEC® CARBA NP and inactivation respectively. Conclusion: Detection of the 11.109 Da peak confirms the presence of KPC-type carbapenemase, thus saving time and costs by detecting KPC-type carbapenemases simultaneously with identification; a negative result does not rule out the presence of the enzyme. The circulation of transposons other than Tn4401a requires the use of additional tests.